Large-Scale Analysis of Fitness Cost of tet(X4)-Positive Plasmids in Escherichia coli - Tang, Feifei; Cai, Wenhui; Jiang, Lijie; Wang, Zhiqiang; Liu, Yuan (Frontiers in Cellular and Infection Microbiology, 2022)
Tigecycline is one of important antimicrobial agents for the treatment of infections caused by multidrug-resistant (MDR) Gram-negative bacteria. However, the emergence and prevalence of plasmid-mediated tigecycline resistance gene tet(X4) is threatening human and animal health. Fitness cost elicited by resistance plasmids is a key factor affecting the maintenance and transmission of antibiotic resistance genes (ARGs) in host. Comparative analysis of the fitness cost of different types of tet(X4)-positive plasmids is helpful to understand and predict the prevalence of dominant plasmids. In this study, we performed a large-scale analysis of fitness cost of tet(X4)-positive plasmids origin from clinical isolates. These plasmids were successfully electroporated into a reference strain E. coli TOP10, and a series of transformants carrying tet(X) gene was obtained. The effect of tet(X4)-positive plasmids on growth rate, plasmid stability, relative fitness, biofilm formation and virulence in a Galleria mellonella model were evaluated. Consequently, we found that these plasmids resulted in varying degrees of fitness cost on TOP10, including delayed bacterial growth and attenuated virulence. Out of these plasmids, tet(X4)-harboring IncFII plasmids showed the lowest fitness cost on host. Furthermore, by means of experimental evolution in the presence of commonly used drugs in clinic, the fitness cost of tet(X4)-positive plasmids was substantially alleviated, accompanying by increased plasmid stability. Collectively, our data reveal the differential fitness cost caused by different types of tet(X4)-positive plasmids, and suggest that the widely use of tetracycline antibiotics may promote the evolution of plasmids.